À propos des espaces d’enseignement et des salles de conférence dans le monde romain - Michèle Villetard (Frontière·s)
It is not completely accurate to think that there were no specific teaching places in the Roman Empire. Literary or epigraphic sources as well as the last fifty years of archaeological works point out that medium and higher-level education could be performed in various types of buildings: small rooms where a few pupils learned or prestigious buildings where orators and sophists recited for hundreds or thousands of auditors. When teaching was performed outdoors, in private or public areas, there was no fence except sometimes light and perishable structures. As for teaching buildings, their inner delimitations could be as various as curtains, doors, columns, or walls of varying heights and thickness, depending on whether they were public or private spaces, isolated buildings or part of cultural or religious complexes, as well as their degree of prestige. However we have to concede that the material nature of these borders is often difficult to identify, primarily because of the limits of our current archaeological knowledge.